Nile tilapia juveniles reared at cold suboptimal water temperatures do not benefit from dietary supplementation with cholesterol - Jorge Filipe Banze; Renata Oselame Nobrega; Bruna Mattioni; Bianca Leticia Richter; Katharinne Ingrid Moraes de Carvalho; Jacó Joaquim Mattos; Maria Risoleta Freire Marques; James Eugene Pettigrew; Débora Machado Fracalossi (Italian Journal of Animal Science)
Cholesterol is important to restructure the phospholipid classes ensuring adequate membrane function at different temperatures. This study aimed to assess the dietary cholesterol supplementation effect on growth, nutrient digestibility, and lipid metabolism of Nile tilapia under suboptimal water temperature (22 °C). Two feeding trials were conducted: a dose-response trial and a subsequent digestibility trial lasting 91 and 30 d, respectively. In the dose-response trial, increasing levels of dietary cholesterol (0, 0.25, 0.5, 0.75, and 1.0%) were fed to juveniles (initial weight 29.24 ± 0.02 g) in six replicates. In the digestibility trial, we tested 0.00 and 0.25% levels in triplicate (initial weight 230.47 ± 1.51 g). Increasing dietary cholesterol supplementation did not affect growth but affected lipid metabolism resulting in increased body and hepatic cholesterol deposition. Additionally, in plasma, we registered an increase in cholesterol and non-HDL lipoproteins but a decrease in the triacylglycerols. Supplementation with 0.5% was enough to reduce the transcription levels of HMGCr – a gene related to cholesterol synthesis in the liver ─ and to promote morphological changes. For instance, congestion and dilation of the sinusoids, intensified macrosteatosis, and loss of hepatocyte nuclei. Dietary cholesterol at 0.25% was sufficient to compromise the digestibility of protein and fatty acids. Despite not affecting Nile tilapia growth, supplementation with cholesterol reduced nutrient digestibility and affected lipid metabolism, resulting in significant changes in the morphology and composition of the liver. Thus, Nile tilapia juveniles do not benefit from dietary supplementation with cholesterol when reared at cold suboptimal water temperatures.